Education in Bhutan Culture, Schooling, and Gross National Happiness / edited by Matthew J. Schuelka, T.W. Maxwell. - Schuelka, Matthew J.; Schuelka, Matthew J.; Maxwell, T.W.; Maxwell, T.W. (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2016)
Bhutan is a country in the Himalayas with a relatively new education system and a unique governmental philosophy known as Gross National Happiness. This book explores the history, culture, challenges, and opportunities of schooling in Bhutan. It discusses topics including historical perspectives on Buddhist monastic education, the regional and international influence on educational development, traditional medical education, higher education, and the evolution of Bhutanese educational policy, to name but a few. It also investigates contemporary challenges to schooling in Bhutan such as adult education, inclusive education, early childhood education, rurality, and gender. Throughout the book, the developmental philosophy of Gross National Happiness is explored as a novel and culturally vital approach to education in Bhutan. The majority of the authors are prominent Bhutanese scholars and educational leaders, with select non-Bhutanese international scholars with strong links to Bhutan also contributing. This book is a valuable resource not only for those specifically interested in education in Bhutan, but for anyone with an interest in South Asian studies, general Asian studies, educational development, comparative education, Buddhist education, and the Gross National Happiness development philosophy.